The Strategic Leadership Role in Managing Crisis: Case Study During the Covid-19 Pandemic and the Lebanese Financial Crisis - Maria FRANGIEH; Daniel RUSU (Communications of International Proceedings, 2021)
This article examines the role of strategic leadership in crisis management. Each enterprise is vulnerable and at risk of shutting down if left without reaction. While all surviving enterprises are still trying to cope with the Covid19 pandemic effects, Lebanon is facing another type of crisis: a non-anticipated financial calamity, that blew up in October 2019 and which after-effects are still popping out a day after another, riskier and more disastrous. In the articles’ first part, the concept of crisis, strategic leadership, and crisis management were briefly explained. To detect the strategic leaders’ performances in crisis time, primary data was needed. The selected approach was quantitative. Data was collected through a survey conducted with a sample of twenty-seven Lebanese managers of skin care and cosmetic product shops during March 2021. This sector was specifically selected due to many reasons. First, it is based on selling non-necessity products, which are not clients’ primary needs. Therefore, in time of lockdown and financial crisis, one can assume that this range of products would not sell. However, the contrary was observed: somehow, in the heart of the crisis, these enterprises are still operating and surviving. This raised the importance of the strategic leadership’s effect on containing the crisis. They were asked about their strategic role in this hard time, notably when instilling a long-term organization vision of growth, identifying, conserving, and diversifying the firm’s core competencies, improving and developing human capital, and supervising the strategy execution process, adjusting and improving it.
Keywords: Crisis Management; Strategy; Strategic Leadership; SMEs